2020
DOI: 10.1039/d0ra09413g
|View full text |Cite
|
Sign up to set email alerts
|

Linear consecutive hexaoxazoles as G4 ligands inducing chair-type anti-parallel topology of a telomeric G-quadruplex

Abstract: G-quadruplex structures (G4s) in guanine-rich regions of DNA play critical roles in various biological phenomena, including replication, translation, and gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…19 F is not naturally present in the intracellular space; the 19 F-detected in-cell NMR spectra are free of spectral background. Xu et al showed that the 3,5-bis(trifluoromethyl)phenyl group ( Figure 4 A), referred to as 19 F-probe onwards, linked to 5’-terminus of DNA allows discrimination of G4 topologies using 19 F-detected in-cell NMR [ 37 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…19 F is not naturally present in the intracellular space; the 19 F-detected in-cell NMR spectra are free of spectral background. Xu et al showed that the 3,5-bis(trifluoromethyl)phenyl group ( Figure 4 A), referred to as 19 F-probe onwards, linked to 5’-terminus of DNA allows discrimination of G4 topologies using 19 F-detected in-cell NMR [ 37 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…We have developed a series of polyoxazoles as G4 ligands, 43,44 and found that one of the linear-consecutive hexaoxazole series (6LCOs) selectively induces specific topology of telomeric G4. 45 The G4 ligand L2H2-2M2EA-6LCO (6LCO) was designed based upon the two-point recognition concept, i.e., targeting the G-quartet plane and the groove, and was synthesized as described in our previous report. 45 Here, we show that the enzymatic function of thrombin can be controlled by regulating the binding of thrombin with TBA through the induction of a specific TBA G4 topology with 6LCO (Fig.…”
mentioning
confidence: 99%
“…45 The G4 ligand L2H2-2M2EA-6LCO (6LCO) was designed based upon the two-point recognition concept, i.e., targeting the G-quartet plane and the groove, and was synthesized as described in our previous report. 45 Here, we show that the enzymatic function of thrombin can be controlled by regulating the binding of thrombin with TBA through the induction of a specific TBA G4 topology with 6LCO (Fig. 1C).…”
mentioning
confidence: 99%
See 1 more Smart Citation